ANALISIS YURIDIS PELANGGARAN ZONA EKONOMI EKSKLUSIF OLEH KAPAL ASING DI LAUT NATUNA UTARA BERDASARKAN UNCLOS 1982 - Shafa Yunma Az Zahra; Amira Lutfia (STKIP Subang, 2026)
The North Natuna Sea is part of Indonesia's Exclusive Economic Zone (EEZ) and holds significant economic, geopolitical, and national security value. Although its legal status has been established under the United Nations Convention on the Law of the Sea (UNCLOS) 1982, the area continues to experience various violations. These include illegal fishing activities conducted by foreign vessels and China's unilateral claim through the nine-dash line, both of which have created legal challenges in the region. This study aims to analyze the legal framework governing the EEZ under UNCLOS 1982, identify the forms of violations occurring in the North Natuna Sea, and examine the international legal mechanisms available to Indonesia in addressing those violations. This research employs a normative juridical method using statutory and case approaches. The data were collected through library research, including UNCLOS 1982, Indonesian legislation, legal literature, and the 2016 South China Sea Arbitration award. The findings indicate that Indonesia has a strong legal basis for its sovereign rights over the North Natuna Sea under Articles 55–75 of UNCLOS 1982. Furthermore, the violations that have occurred, including the incidents between December 2019 and January 2020, are inconsistent with the provisions of international law of the sea. To respond to these violations, Indonesia may strengthen law enforcement at sea, pursue diplomatic efforts, and make use of international dispute settlement mechanisms such as the International Tribunal for the Law of the Sea (ITLOS) and arbitral tribunals. The consistent implementation of these measures is expected to reinforce Indonesia's sovereign rights and safeguard its national interests in the North Natuna Sea.